The Impact of Urban Requalification on Municipal Governance: an Analysis from Mozambique - Jochua Abrão Baloi (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2019)
The purpose of this article is to analyze the impact of urban requalification on municipal governance, taking as a starting point the Mozambican reality. The central argument is that the urban requalification had a positive impact on the municipal governance process and contributed to local development. Thus, the question that guides this article is what is the impact of urban requalification on municipal governance in Chamanculo "D" neighborhood? Therefore, this article concludes that requalification is one of the means by which the municipality of Maputo has served in its governance process to inculcate local development.